‘Breaking Through the Waves and Tides’: Rethinking Modernity in Qingdao, China - Shen Hou (Global Environment)
Qingdao is a coastal Chinese city that was founded at the end of the nineteenth century. First established as a German colony and later evolving into a Chinese cosmopolis, Qingdao is now home to several million people, offering its citizens the opportunity to make a living while also enjoying the nearby sea and beaches. By contextualising the story of a local labourer called Hou Wu (侯五) and his descendants, this article illuminates the city’s cultural and environmental transformation in the first half of the twentieth century, especially with regard to its beaches, and discusses the lives and desires of its residents. The article argues that the emerging modern city by the sea was not merely a result of Western colonisation blending with a traditional Chinese aesthetic appreciation of the ocean, but was also in many ways shaped by local people’s inner desires for proximity to the ocean, for playfulness and for enjoying a good life.